Developmen Of Digital Scrapbook Learning Media On Human System Excretion For Grade 8th Junior High School - putri ameliasari; Latisma Dj (Department of Science Education, 2022)
Learning media are tools used to help convey learning material in the teaching and learning process so that it makes it easier to achieve learning objectives. To increase students 'interest in reading learning media, learning media is needed that can attract students' attention, one of which is scrapbook. Scrapbook is a book made by attaching pictures or words and inscriptions on the book. Along with advances in technology, scrapbooks can also be made digitally and can be accessed using cellphones and computers. This type of research is development research using a 4-D model consisting of define, design, develop and disseminate. but the disseminate was not done. In the field of definition, it consists of beginning-end analysis, student analysis, task analysis, concept analysis and learning objective analysis. At the design stage, a digital scrapbook learning media is designed. At the development stage, a validator test was carried out, namely a science education lecturer at FMIPA UNP and a practical test by grade 8th teachers and students of the Darul Falah Lubuk Tarok Islamic Boarding School. human excretion system material can be used as a learning medium, with the high validity category of the validator. The level of practicality of digital scrapbook learning media with a high category by the teacher and a very high category for students